PROBLEM BASED LEARNING BERBANTU ALAT PERAGA MATERI GEOMETRI PADA SISWA KELAS VII SMP REWARANGGA ENDE - Finsensius Yesekiel Naja; Agustina Mei; Sofia Sao (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The process of learning mathematics still uses conventional methods where the teacher dominates the learning process, so still experience learning difficulties, especially understanding concepts and mastery of geometry which causes learning outcomes to decline. This causes students to be passive and only accept the teacher's explanation in other words students are not directed to think to find solutions to the problems at hand. Problem-based learning is learning that makes students active and can find their concepts and be more effective. In addition to problem-based learning. learning must use media that support a more effective teaching and learning process. The use of teaching aids is very influential on the success of the teaching and learning process. The type of this research is experimental research and quantitative approach. The population in this study were all students of class VII SMP Rewarangga while the sample was taken by random sampling totaling 14 students. The data analysis technique used Covariance Analysis (ANACOVA). The learning device meets the requirements of validity, and good sensitivity reliability. The learning tools include Learning Implementation Plans (RPP), Student Worksheets (LKS), and Learning Outcomes Test (THB). Based on the results of Anacova with homogeneity test, from the calculations obtained F count = 1.0787 and F table¬ with a significance level of 5% = 1.98, so F count < F table causes to accept H0 and reject H1 which shows the variance of the two samples is homogeneous. This shows that problem-based learning assisted by teaching aids can improve student learning outcomes for geometry material.